Artistic negotiation, religious and cultural values: an Islamic dance aesthetic in the perspective of Muhammadiyah tarjih decision - Siswantari, Heni; Ahimsa-Putra, Heddy Shri; Maarif, Samsul (International Journal of Visual and Performing Arts, 2024)
This research aims to show the efforts to build Islamic dance aesthetics through artistic negotiations of dance works with art norms in tarjih decisions and cultural values in Muhammadiyah dance performances. The results of this intersection gave rise to a new value in Islamic dance art that speaks not only to divine oneness as an Islamic principle but also to Indonesian cultural factors in its aesthetic performance. Data was collected for 6 months using interview techniques and audio-visual data analysis of 3 dance works and artists in Muhammadiyah. Interviews with the general chairman policymakers in the field of tarjih and art institutions in Muhammadiyah also support analysis related to religious values in artworks.Â  The analysis shows that the dance works performed result from the artist's religious interpretation of the norms in the Muhammadiyah tarjih decision. There is a negotiation between artists and Muhammadiyah administrators that takes place continuously in Muhammadiyah dance performances. Artists conduct artistic negotiations in the dance works performed to harmonize with Islamic values without eliminating cultural elements. The adaptation process is more on content (variety of dance movements), performance (costumes and dance supporting elements), and ideas (philosophical values within the cultural framework). The theoretical contribution of this research is to understand the relationship between art, culture, and religion, especially in the context of Islamic performing arts. This research also makes an important contribution to building the theory of Islamic dance aesthetics, which talks about artistic beauty and religious meaning in every element of performing arts and shows it through the perspective of dance diversity in Indonesia.